RESTORASI PERAN PENDIDIKAN ISLAM DALAM TATANAN KEHIUPAN SOSIAL - Moh. Afiful Khair Moh. Afiful Khair (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
This paper describes some of Muslim’s social problems in Indonesia,as like, social conflicts have been caused by different backgrounds, proverty, and life dis-orientation. It also concerns about the real conditionthat Islamic education which has not been given the contribution more toward the improvement of the condition. Finally, this paper suggests the importance of Islamic education to imply the human nature potential development to create well-conduct of human beings, exactly the human of individual both the spritual piety and social concern.